The vibration plethysmographic method of arterial compliance analysis in dependence on transmural pressure - Moudr, J; Svačinová, J; Závodná, E; Honzíková, N (Physiological research, 2014)
The aim of this study was to obtain a detailed analysis of the relationship between the finger arterial compliance C [ml/mm Hg] and the arterial transmural pressure P(t) [mm Hg]. We constructed a dynamic plethysmograph enabling us to set up a constant pressure P(css) [mm Hg] and a superimposed fast pressure vibration in the finger cuff (equipped with a source of infra-red light and a photoelectric sensor for the measurement of arterial volume). P(css) could be set on the required time interval in steps ranging between 30 and 170 mm Hg, and on sinusoidal pressure oscillation with an amplitude P(ca) (2 mm Hg) and a frequency f (20, 25, 30, 35, 40 Hz). At the same time continuous blood pressure BP was measured on the adjacent finger (Portapres). We described the volume dependence of a unitary arterial length on the time-varying transmural pressure acting on the arterial wall (externally P(css)+P(ca).sin(2pif), internally BP) by a second-order differential equation for volume. This equation was linearized within a small range of selected BP. In the next step, a Fourier transform was applied to obtain the frequency characteristic in analytic form of a complex linear combination of frequency functions. While series of oscillations [P(ca), f] were applied for each P(css), the corresponding response of the plethysmogram was measured. Amplitude spectra were obtained to estimate coefficients of the frequency characteristic by regression analysis. We determined the absolute value: elastance E, and its inverse value: compliance (C=1/E). Then, C=C(P(t)) was acquired by applying sequences of oscillations for different P(css) (and thus P(t)) by the above-described procedure. This methodology will be used for the study of finger arterial compliance in different physiological and pathological conditions.
Keywords: Female; Fingers; Plethysmography; Compliance; vibrace; mladý dospělý; ženské pohlaví; lidé; krevní tlak; Vibration; modely kardiovaskulární; Arteries; Male; Aged; Young Adult; pletysmografie; diagnostické techniky kardiovaskulární; prsty ruky; senioři; mužské pohlaví; Models, Cardiovascular; Diagnostic Techniques, Cardiovascular; Blood Pressure; arterie; poddajnost; Humans